Tofacitinib Downregulates TNF and Poly(I:C)-Dependent MHC-II Expression in the Colonic Epithelium - Gopalakrishnan, Shreya; Hansen, Marianne Doré; Skovdahl, Helene Kolstad; Roseth, Ingrid Aass; van Beelen Granlund, Atle; Østvik, Ann Elisabet; Bakke, Ingunn; Sandvik, Arne Kristian; Bruland, Torunn (Frontiers in Immunology, 2022)
Major Histocompatibility Complex (MHC)-I and -II genes are upregulated in intestinal epithelial cells (IECs) during active inflammatory bowel diseases (IBD), but little is known about how IBD-relevant pro-inflammatory signals and IBD drugs can regulate their expression. We have previously shown that the synthetic analog of double-stranded RNA (dsRNA) Polyinosinic:polycytidylic acid (Poly(I:C)), induces interferon stimulated genes (ISGs) in colon organoids (colonoids). These ISGs may be involved in the induction of antigen presentation. In the present study, we applied colonoids derived from non-IBD controls and ulcerative colitis patients to identify induction and effects of IBD-drugs on antigen presentation in IECs in the context of Tumor Necrosis Factor (TNF)-driven inflammation. By RNA sequencing, we show that a combination of TNF and Poly(I:C) strongly induced antigen-presentation gene signatures in colonoids, including expression of MHC-II genes. MHC-I and -II protein expression was confirmed by immunoblotting and immunofluorescence. TNF+Poly(I:C)-dependent upregulation of MHC-II expression was associated with increased expression of Janus Kinases JAK1/2 as well as increased activation of transcription factor Signal transducer and activator of transcription 1 (STAT1). Accordingly, pre-treatment of colonoids with IBD-approved pan-Janus Kinase (JAK) inhibitor Tofacitinib led to the downregulation of TNF+Poly(I:C)-dependent MHC-II expression associated with the abrogation of STAT1 activation. Pre-treatment with corticosteroid Budesonide, commonly used in IBD, did not alter MHC-II expression. Collectively, our results identify a regulatory role for IBD-relevant pro-inflammatory signals on MHC-II expression that is influenced by Tofacitinib.